2014
DOI: 10.1016/j.ajpath.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a-3p Inhibits Aurora Kinase A and Attenuates Prostate Cancer Growth

Abstract: Copyright: Epis et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACT RNA-based therapeutics could represent a new avenue of cancer treatment. miRNA 331-3p (miR-331-3p) is implicated in prostate cancer (PCa) as a putative tumor suppressor, but its functional activity and synergy with other anti-tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…We are the first to show a strong correlation between high active b-catenin immunohistochemical expression and high Gleason score prostate tumors. Many studies have linked overexpression of AurKA with progression and malignant phenotype of prostate cancers (41)(42)(43)(44), although there are controversial results with respect to its correlation with the Gleason score (45,46). We observed a significant correlation between high expression of AurKA and high Gleason score tumors.…”
Section: Discussionsupporting
confidence: 64%
“…We are the first to show a strong correlation between high active b-catenin immunohistochemical expression and high Gleason score prostate tumors. Many studies have linked overexpression of AurKA with progression and malignant phenotype of prostate cancers (41)(42)(43)(44), although there are controversial results with respect to its correlation with the Gleason score (45,46). We observed a significant correlation between high expression of AurKA and high Gleason score tumors.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, miRNAs are now recognized as key post-transcriptional regulators of gene expression. Although miR-199a-3p has been reported to attenuate xenograft tumor growth of prostate carcinoma by targeting Aurora-A [38], the expression of miR-199a-3p showed no difference between HCC tissues with or without LNM from our miRNA array data and by qRT-PCR (data not shown). A single gene can be regulated by several miRNAs, while a single miRNA can regulate multiple target genes within the same or different tissues.…”
Section: Discussionmentioning
confidence: 61%
“…Tao et al studies have shown that miR-133 inhibits cell proliferation, migration, and invasion in PCa cells by targeting the epidermal growth factor receptor [122]. The ability of let-7 to inhibit tumor initiation was first demonstrated in a murine CD44-positive xenograft model, where overexpression and therapeutic injection of let-7 retarded tumor growth [123][124][125]. Intratumoral administration of miR-199a-3p mimics into a murine PCa-xenograft model led to decreased expression of the oncogene Aurora kinase A (AurkA), which is associated with a malignant PCa phenotype [125].…”
Section: Mirnas As Therapeutic Tool In Prostate Cancermentioning
confidence: 98%
“…The ability of let-7 to inhibit tumor initiation was first demonstrated in a murine CD44-positive xenograft model, where overexpression and therapeutic injection of let-7 retarded tumor growth [123][124][125]. Intratumoral administration of miR-199a-3p mimics into a murine PCa-xenograft model led to decreased expression of the oncogene Aurora kinase A (AurkA), which is associated with a malignant PCa phenotype [125]. In another murine xenograft model, using transfected PCa cell lines [124], miR-128 showed antiproliferative as well as proapoptotic effects and negatively regulated PCa stem cells by directly targeting the stem cell-related genes Bmi-1 and Nanog (Nanog homeobox).…”
Section: Mirnas As Therapeutic Tool In Prostate Cancermentioning
confidence: 99%